2008
DOI: 10.1017/s0950268808001477
|View full text |Cite
|
Sign up to set email alerts
|

An ecological analysis of sociodemographic factors associated with the incidence of salmonellosis, shigellosis, and E. coli O157:H7 infections in US counties

Abstract: Identifying county-level sociodemographic and economic factors associated with the incidence of enteric disease may provide new insights concerning the dynamics of community transmission of these diseases as well as opportunities for prevention. We used data from the National Notifiable Diseases Surveillance System, the U.S. Census Bureau, and the Health Resources and Services Administration to conduct an ecological analysis of 26 sociodemographic and economic factors associated with the incidence of salmonell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 44 publications
3
70
2
Order By: Relevance
“…3). Similarly, Chang et al (2009) found that salmonellosis incidence rates were moderately positively correlated with higher percentages of the population (at the county-level) composed of African Americans (Chang et al, 2009). In addition, in a recent survey of consumers in FoodNet sites that evaluated exposures of children to raw meat and poultry in grocery stores and shopping carts, exposure of children to raw products was higher among African American children compared to Caucasian children (Patrick et al, 2010).…”
Section: Community Socioeconomic Factorsmentioning
confidence: 95%
See 3 more Smart Citations
“…3). Similarly, Chang et al (2009) found that salmonellosis incidence rates were moderately positively correlated with higher percentages of the population (at the county-level) composed of African Americans (Chang et al, 2009). In addition, in a recent survey of consumers in FoodNet sites that evaluated exposures of children to raw meat and poultry in grocery stores and shopping carts, exposure of children to raw products was higher among African American children compared to Caucasian children (Patrick et al, 2010).…”
Section: Community Socioeconomic Factorsmentioning
confidence: 95%
“…In three of the seven FoodNet sites studied (Maryland, New Mexico and Tennessee), higher poverty levels in zip codes were associated with higher rates of infection with one or more Salmonella serotypes. Chang et al (2009) previously identified a positive association between poverty levels and salmonellosis incidence rates at the county-level (Chang et al, 2009). More recently, in a Canadian study, Pardhan-Ali et al (2013) showed that rates of Salmonella infection were positively associated with the number of "households in core need" (homes that fall below defined standards and have low household incomes) (Pardhan-Ali et al, 2013).…”
Section: Community Socioeconomic Factorsmentioning
confidence: 95%
See 2 more Smart Citations
“…Worldwide, approximately 1.7 million deaths per year from infectious diarrhoea are attributable to these three factors [21]. Recent epidemiological results highlight the importance of socioeconomic risk factors in rates of disease associated with E. coli O157 [22]. Nevertheless, how socioeconomic level relates to these individual risk factors is unknown and warrants further evaluation [23].…”
Section: Introductionmentioning
confidence: 99%